The Relationship of Student Process Skills to Student Responses with the Student Team Achievement Division (STAD) Learning Model in Elementary Schools and Madrasah Ibtidaiyah - Kamid Kamid; Sri Winarni; Rohati Rohati; Wahyu Adi Pratama (STAI Hubbulwathan Duri, 2022)
Abstract Effective learning can be increased by forming several groups that have diversity in abilities, gender, and ethnicity. So this research was conducted with the aim of knowing the relationship between students' process skills on student responses to the Student Team Achievement Division (STAD). learning model for the volume of blocks and cubes. This research is a survey research, this study uses quantitative data analysis with the help of SPSS statistics 25, to find descriptive statistics, test assumptions and test hypotheses. The results obtained from this study were conducted in 4 schools, namely 2 SD and 2 MI with 36 students in each class. So the total number of students is 144 students. Based on the T test, the results showed that there were significant differences in students' process skills in students' responses to the Student Team Achievement Division (STAD). learning model for the volume of blocks and cubes between schools. Based on the correlation test, it was concluded that there was a relationship between students' process skills on student responses with the Student Team Achievement Division (STAD). learning model for the inter-school volume of blocks and cubes. the writer gives suggestions, namely the implementation of the Student Team Achievement Division (STAD) cooperative learning model as an effort to improve Student Process Skills. Abstrak Pembelajaran yang efektif dapat ditingkatkan dengan membentuk beberapa kelompok yang mempunyai keragaman dalam kemampuan, jenis kelamin, hingga sukunya. Sehingga penelitian ini dilakukan dengan tujuan untuk mengetahui hubungan antara keterampilan proses siswa pada respon siswa dengan model Pembelajaran Student Team Achievement Division (STAD) materi volume balok dan kubus. Penelitian ini merupakan penelitian survey, penelitian ini menggunakan analisis data kuantitatif dengan bantuan SPSS statistic 25, untuk mencari statistik deskriptif, Uji asumsi dn Uji Hipotesis. Hasil yang diperoleh dari Penelitian ini dilakukan pada 4 sekolah yaitu 2 SD dan 2 MI dengan masing-masing kelas berjumlah 36 siswa. Sehingga total siswa keseluruhan yaitu 144 siswa. Berdasarkan uji T didapat hasil terdapat perbedaan yang signifikan pada keterampilan proses siswa pada respon siswa dengan model Pembelajaran Student Team Achievement Division (STAD) materi volume balok dan kubus antar Sekolah. Berdasarkan uji korelasi disimpulkan bahwa terdapat hubungan antara keterampilan proses siswa pada respon siswa dengan model Pembelajaran Student Team Achievement Division (STAD). materi volume balok dan kubus antar sekolah. maka penulis memberikan saran yaitu pada pelaksanaan model pembelajaran kooperatif tipe Student Team Achievement Division (STAD) sebagai upaya untuk meningkatkan Keterampilan Proses Siswa.